Distant Teaching and Learning for the Foreseeable Future: Georgian Universities’ Students and Professors Perspective - Akhvlediani, Maia; Moralishvili, Sophio; Kuprashvili, Levan (European Journal of Social Science Education and Research, 2022)
Like the rest of the world, because of COVID-19 and the new reality, most professors and students suddenly have found themselves forced to use technology while teaching and learning. All of a sudden, every faculty member faced the challenge of delivering education online and accordingly every student receiving education online. On the other hand, it was an overwhelming time for the administration to achieve quality online education at scale. Nevertheless, most universities in Georgia immediately took the challenges of converting to asynchronous learning. The paper presents findings of the survey conducted at the present stage at Georgian private and state universities, comparing students’ and professors’ satisfaction with e-learning. Surprisingly, it appears that professors feel better motivated with online teaching rather than students. Almost every respondent agrees that what seems like the best-case scenario out of this crisis needs much stronger contribution and elaboration in the years ahead.